Applying ergonomics within the multi-modelling paradigm with an example from multiple UAV control. - Golightly, David; Gamble, Carl; Palacin, Roberto; Pierce, Ken (Ergonomics, 2020)
This article presents a position statement on using ergonomics in conjunction with the multi-modelling paradigm. Multi-modelling is a computational approach to combine models of systems and components for design and simulation of cyber physical systems and systems of systems. Despite potentially significant benefits in terms of more human-centric system modelling, there is limited evidence of the application of ergonomics within multi-modelling. This article presents the case for applying ergonomics within multi-modelling. We open with an introduction to multi-modelling and benefits, applications and gaps for ergonomics in multi-modelling, and of potentially useful models from ergonomics. We then describe a proof-of-concept implementation of ergonomics within a multi-model of UAV control. This demonstrates that as well as user-centred modelling, this approach supports ergonomics in how we can access rich systems models, and the collaborative value of applying ergonomics theory in systems design. Practitioner Summary: Examines multi-modelling, a computational approach for complex modelling, and the contribution of ergonomics. An autonomous UAV test implementation demonstrates the application of ergonomics knowledge for improving design and evaluation processes, and how multi-modelling can give ergonomics access to rich systems models. Abbreviations: ACT-R: adaptive control of thought—rational; API: application programming interface; CFD: computational fluid dynamics; COTS: commerical off the shelf; CPS: cyber-physical system; CT: continuous time; DE: discrete event; DSE: design space exploration; FME: finite element modeling; FMI: functional mock-up interface; FMU: functional mock-up unit; GOMS: goals, operators, methods, selections; HCI: human-computer interaction; IMPRINT: improved performance research integration tool; INTO-CPS: integrated toolchain for cyber-physical system modeling; KLM: keystroke level model; MPC: model-predictive control; SysML: system markup language; SoS: system of system; UAV: unmanned aerial vehicle